Effect of the composite surface sealant application moment on marginal sealing of compactable composite resin restoration - Delfino, Carina Sincler; Duarte, Sillas (Springer, 2007)
An analysis was carried out to observe whether the application or not of a composite surface sealant (CSS), as well the moment for CSS application were able to reduce marginal microleakage in compactable composite resin restoration. All the preparations were restored with a compactable composite resin. The restored teeth were randomly assessed. G1 (control group): finished and polished; G2: finished, polished, etched and cover with CSS; G3: immediately after the restoration done the CSS was applied, then finished and polished; G4: CSS applied immediately after the restoration was done, the finished and polished, etched, and covered with CSS. The specimens were isolated with nail polish, thermocycled, immersed in aqueous solution of silver nitrate, and followed in a photo developing solution. The microleakage scores obtained from the occlusal and cervical walls were analyzed with the Kruskall-Wallis nonparametric test. No microleakage was found at the enamel margins. Comparing the microleakage scores at dentin/cementum margins (p < 0.05) it was found that G3 (p = 0.0162) and G4 (p = 0.0187) were able to reduce microleakage when compared with group G2. However the results were not statistically different from the control group. The application of CSS was not able to completely eliminate marginal microleakage at the dentin/cementum margins.